The Effect Of Education On The Utilization Of Kitchen Seasoning As Infused Water To Increase The Immunity Of The Community Of Sukamukti Village - Aji Najihudin; Syifa Rizkia Khoerunisa; Esa Syarifulbanat; Fitria Suryani; Fitri Apriyani (Fakultas Kewirausahaan Universitas Garut, 2022)
Abstract Education on the use of herbs as infused water is a way to increase public knowledge about the properties and use of herbs as herbal medicine. This community service activity aims to determine the effect of education on the use of kitchen spices as infused water to increase the immunity of the people of Sukamukti Village. The service was carried out in Sukamukti Village, Cilawu District, Garut Regency, West Java. With PKK respondents as many as 10 people from Kp. KondangRege Sukamukti Village. The method used in this research was education on the use of spices as infused water to increase immunity and showing training videos for making kitchen spices infused water. Evaluation is done by giving questionnaires to respondents before and after education. The final result is an increase in knowledge of 38% on the educational effect of using herbs as infused water Abstrak Edukasi pemanfaatan bumbu dapur sebagai infused water adalah suatu cara untuk meningkatkan pengetahuan masyarakat mengenai khasiat dan pemanfaatan bumbu dapur sebagai obat herbal. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk mengetahui pengaruh edukasi pemanfaatan bumbu dapur sebagai infused water untuk meningkatkan imunitas masyarakat Desa Sukamukti. Kegiatan pengabdian dilaksanakan di Desa Sukamukti Kecamatan Cilawu Kabupaten Garut Jawa Barat. Dengan responden ibu-ibu PKK sebanyak 10 orang dari Kp. KondangRege Desa Sukamukti. Metode yang digunakan pada penelitian yaitu edukasi penyuluhan pemanfaatan bumbu dapur sebagai infused water untuk meningkatkan imunitas dan penayangan video pelatihan pembuatan infused water bumbu dapur. Evaluasi dilakukan dengan memberikan kuesioner kepada responden sebelum maupun sesudah dilakukannya edukasi. Didapatkan hasil akhir yaitu peningkatan pengetahuan sebesar 38% terhadap pengaruh edukasi pemanfaatan bumbu dapur sebagai infused water.